2022
DOI: 10.3390/cryst12030384
|View full text |Cite
|
Sign up to set email alerts
|

Study of Radiation Resistance to Helium Swelling of Li2ZrO3/LiO and Li2ZrO3 Ceramics

Abstract: The key aim of this paper is to study the presence effect of LiO impurity phases in Li2ZrO3 ceramics on the resistance to helium swelling and structural degradation during implanted helium accumulation in the near-surface layer structure. The hypothesis put forward is based on a number of scientific papers, in which it was reported that the presence of two or more phases in lithium-containing ceramics led to a decrease in the rate of radiation damage and gas swelling due to the presence of additional interfaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In the irradiation case, the deformation increases or decreases because of tensile stresses. As a result, the parameters and volume of the crystal lattice may increase or decrease accordingly [31]. To verify the correctness of the lack of influence of the crystal phase of the Bi:BT sample after radiation, the X-ray data were subjected to Rietveld refinement analysis using the Fullprof software, as shown in Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the irradiation case, the deformation increases or decreases because of tensile stresses. As a result, the parameters and volume of the crystal lattice may increase or decrease accordingly [31]. To verify the correctness of the lack of influence of the crystal phase of the Bi:BT sample after radiation, the X-ray data were subjected to Rietveld refinement analysis using the Fullprof software, as shown in Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
“…Lattice distortion and defect accumulation had an effect on the optical and electrical properties of the investigated samples, as shown in the next sections. Formulas (1) and ( 2) were used to obtain the distortion of the crystal lattice based on changes in the lattice parameters of the crystal and characterize the gamma influence on the crystal lattice [31]:…”
Section: Resultsmentioning
confidence: 99%
“…As is known, the phase composition of ceramics, as well as the presence of impurities in the composition of ceramics, can have both a positive and a negative effect on the strength properties of ceramics, including the resistance to compression and external pressure. In turn, the presence of impurities can have a significant effect on heat transfer in the material, thereby reducing the efficiency of heat removal from ceramics and the occurrence of overheating [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the foregoing, the purpose of this work is to study the effect of the phase composition of Li 2 ZrO 3 ceramics obtained by solid-phase synthesis and annealed at different annealing temperatures in the range from 600 to 1100°C on the strength and thermophysical parameters of ceramics. This work is part of a cycle of works devoted to the study of the Li 2 ZrO 3 ceramic properties and evaluation of the possibility of their use as blanket materials for tritium propagation, which is one of the promising research areas in modern energy [18][19][20]. Li 2 ZrO 3 ceramics were chosen as objects of study, which, as was shown earlier in [18][19][20], are highly resistant to radiation damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation